PENGARUH TANGGUNG JAWAB SOSIAL DAN CITRA PERUSAHAAN TERHADAP PEMBELIAN MEREK AQUA PADA PT TIRTA INVESTAMA CABANG MAKASSAR - A. Hadidu A. Hadidu (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This study aims to determine the effect of analysis Social Responsibility, and Corporate Image To Purchase Brand AQUA PT.Tirta Investama In Makassar Branch. the method used is simple regression analysis method, namely the method is used as a measuring tool in the statistical results of the discussion, and analyzed to provide a complete description of the problem is knowing dihadapi.Metode quantitative increase in purchases in the eyes of consumers. Results showed that Significant effect with the positive direction of the variable anatara corporate social responsibility and corporate image with purchasing decisions Drinking Water AQUA brand by PT.Tirta Investama Makassar branch, because the better the company's image in the eyes of consumers will make consumers increasingly improving is evident by the level pembelian.hal high significance.